Effect of dietary Black pepper (Piper nigrum) on the performance of broiler (Bangladesh Journal of Animal Science, 2015)
An experiment was conducted to determine the dietary effect of different levels of ground black pepper (Piper nigrum) on growth performance and apparent nutrient digestibility of broiler chickens. There were five dietary treatments each containing 0, 0.25, 0.50, 0.75 and 1.00 % black pepper (BP) fed at both starter and finisher phases. One hundred and fifty (150) day old chicks of Arbor-acre strain were divided into five dietary groups having three replication with 10 in each. The five dietary treatments were randomly assigned into five groups. The birds were fed and watered ad libitum. At the starter phase 0.25 and 0.5 % BP improved live weight significantly (p